A green approach for the biosynthesis of powdered silver nanoparticles using leaf extract of Trigonella foenum-graecum L.: Characterization and antibacterial evaluation - Rajkumar, T; Patra, Jayanta Kumar (Bangladesh Journal of Botany, 2019)
Silver nanoparticles (AgNPs) were synthesized using aqueous leaf extract of Trigonella foenumgraecum as reducing and stabilizing agent. The ultraviolet-visible spectrum showed absorption peak at 480 nm. XRD pattern indicates the formation of face-centered cubic structure of silver nanoparticles. FESEM images indicate the presence of spherical silver nanoparticles with the particle size of 90 nm. FTIR indicates that the participation of different functional groups present in the biomolecules is responsible for both reducing and stabilizing the formation of nanoparticles. The synthesized AgNPs demonstrated positive antibacterial activity against two different foodborne pathogenic bacteria (Escherichia coli O157:H7 ATCC 35150, Staphylococcus aureus ATCC 13565) with zones of inhibition of 9.20 ± 0.18 and 9.34 ± 0.11, respectively and MIC and MBC of 100 and >100 μg/ml, respectively. The synthesized AgNPs could serve as a candidate for development of antibacterial drugs or additive in the food packaging system for its application in medicine, cosmetics and food sector industries.